Avaliação da percepção dos serviços em instituições públicas com estruturas administrativas heterogêneas: elaboração e validação de instrumento para avaliação - Cabral, Camila Ines Ribeiro (2021)
Federal higher education institutions (IFES) have high organizational complexity, requiring managers to know the institutional reality and a variety of skills to assist them in the decisionmaking process and in overcoming institutional challenges. Although some IFES follow a pattern of administrative organization, many of these institutions are organized in a heterogeneous way, such as multicampi.In this context, the objective of this work was to develop an instrument that allows managers of multicampi universities to assess the perception of public servants regarding the provision of services in public organizations with heterogeneous administrative structures. Initially, a bibliographic survey was carried out to obtain the conceptual and theoretical approach, as well as the revision of the most used valid instruments for the evaluation of public services. The dimensions and variables were established and the first version of the instrument was developed. Then, the first stage of the test-retest phase was carried out for validation, by applying the instrument to a group of IFES servers. In the third stage, the instrument was subjected to semantic validation by a panel of specialists. In the fourth stage, to complete the test-retest phase, the instrument returned to the sample participating in the second stage to verify the level of understanding of the participants and perform face validation. Finally, the instrument was applied to a group of TAES and professors in charge of IFES leadership to validate the construct and verify reliability. For the calculation of the sample needed for the last stage, the proportion of 3: 1 (participants: question) was considered. The data from the second and fourth stages were analyzed using descriptive statistics and parametric tests for independent samples. For the validation of the construct, in the last methodological step, the Kaiser-Meyer-Olkin (KMO) and Bartlett's sphericity tests were performed. To assess homogeneity, each attribute should have Cronbach's alpha> 0.70. Factors with at least one question with a factor load greater than 0.5 were selected. The three factors obtained from the factor analysis explain a variance of 65.66%. Cronbach's alpha for the 25 variables that make up the validated instrument is greater than 0.90. The instrument has 25 variables divided into three dimensions. In addition to the possibility of assessing the administrative structure by comparing the perception of the ideal service provision and the perception of the service actually provided by the respondent's work unit, the instrument allows the identification of the perception of the servers about what they consider ideal in the structure administrative and management of the institution, providing information that can assist in future decision making, as well as providing an overview of the respondents' perception regarding the provision of services in the researched institution. The use of the validated instrument can result in a proposal for a continuous assessment of heterogeneous administrative structures in public organizations through the analysis of the perception of public servants.